2015
DOI: 10.1016/j.vaccine.2015.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Neutralising antibody response in domestic cats immunised with a commercial feline immunodeficiency virus (FIV) vaccine

Abstract: HighlightsFIV vaccinated cats screened for neutralising antibodiesHomologous neutralisation in 50% of cats testedNo heterologous neutralisation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 56 publications
0
15
0
1
Order By: Relevance
“…The VGG has also reconsidered the FIV vaccine, which in previous iterations of these guidelines has been categorized as 'not recommended'. The basis for this categorization was: (1) questions over the cross-protection between subtypes of virus included in the vaccine and those subtypes and recombinants in the field in different geographical areas (Hosie et al 1995, Dunham et al 2006, Yamamoto et al 2007, Coleman et al 2014, Beczkowski et al 2015a [EB1], (2) the interference of the vaccine with antibody testing used for diagnosis of FIV infection (Hosie & Beatty 2007) [EB1], and (3) the fact that this is an adjuvanted vaccine that must be given repeatedly (a primary course of three injections and annual revaccination) to a species susceptible to injection site sarcoma. The VGG is aware that in some parts of the world, there remains a significant prevalence of FIV seropositivity and/or infection (Bennett et al 1989, Hosie et al 1989, Friend et al 1990, Glennon et al 1991, Bandecchi et al 1992, Hitt et al 1992, Ueland and Lutz 1992, Jones et al 1995, Hofmann-Lehmann et al 1996, Yilmaz et al 2000, Lee et al 2002, Muirden 2002, Norris et al 2007, Gleich et al 2009, Ravi et al 2010, Bande et al 2012, Chang Fung Martel et al 2013, Rypula et al 2014 [EB1].…”
Section: Vaccination Of Individual Catsmentioning
confidence: 99%
“…The VGG has also reconsidered the FIV vaccine, which in previous iterations of these guidelines has been categorized as 'not recommended'. The basis for this categorization was: (1) questions over the cross-protection between subtypes of virus included in the vaccine and those subtypes and recombinants in the field in different geographical areas (Hosie et al 1995, Dunham et al 2006, Yamamoto et al 2007, Coleman et al 2014, Beczkowski et al 2015a [EB1], (2) the interference of the vaccine with antibody testing used for diagnosis of FIV infection (Hosie & Beatty 2007) [EB1], and (3) the fact that this is an adjuvanted vaccine that must be given repeatedly (a primary course of three injections and annual revaccination) to a species susceptible to injection site sarcoma. The VGG is aware that in some parts of the world, there remains a significant prevalence of FIV seropositivity and/or infection (Bennett et al 1989, Hosie et al 1989, Friend et al 1990, Glennon et al 1991, Bandecchi et al 1992, Hitt et al 1992, Ueland and Lutz 1992, Jones et al 1995, Hofmann-Lehmann et al 1996, Yilmaz et al 2000, Lee et al 2002, Muirden 2002, Norris et al 2007, Gleich et al 2009, Ravi et al 2010, Bande et al 2012, Chang Fung Martel et al 2013, Rypula et al 2014 [EB1].…”
Section: Vaccination Of Individual Catsmentioning
confidence: 99%
“…In the remaining two positive cats, one (C171) had a strain most closely related to the Sendai1 strain, a FIV subtype A from Japan (D37814) (91% similarity, 32/374), and the other (C181) a strain with 91% similarity to UK2 strain and Sendai1 strain (38/374). (Table 2) [26]. …”
Section: Resultsmentioning
confidence: 99%
“…Five were most closely related to the UK2 strain, a FIV subtype A from Scotland (X69496), with 94–95% similarity (38–43 mismatches) to C171, C172, C174, C176 and C180 (Table 3) [19]. The other three positivities were most closely related to FIV subtype A/B strain FDSydneyC36 from Australia (KP330229) which had 94% (636/677) identity with C18, 96% (652/683) identity with C78 and 95% (638/680) identity with C181, respectively (Table 3, Fig 1) [26]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the result from Study 1 is not statistically significant, T cells appeared to be involved in conferring A-T protection, but the number of B-cell recipients was too small to determine whether B cells alone can confer A-T protection. In regards to the potential of B cells to afford protection to recipients of A-T, studies by others have shown that the commercial dual-subtype FIV vaccine [31] as well as priming T cells with FIV Pet Env pDNA [32] induced high NAbs to FIV Pet . However, in current studies, all recipients of A-T from vaccinated cats, except for the unprotected recipients, had no NAbs to FIV Pet or FIV FC1 (data not shown) and no FIV Abs (Tables 2 and 3, immunoblot).…”
Section: Discussionmentioning
confidence: 99%